2016
DOI: 10.1155/2016/7139852
|View full text |Cite
|
Sign up to set email alerts
|

Server Resource Dimensioning and Routing of Service Function Chain in NFV Network Architectures

Abstract: The Network Function Virtualization (NFV) technology aims at virtualizing the network service with the execution of the single service components in Virtual Machines activated on Commercial-off-the-shelf (COTS) servers. Any service is represented by the Service Function Chain (SFC) that is a set of VNFs to be executed according to a given order. The running of VNFs needs the instantiation of VNF instances (VNFI) that in general are software components executed on Virtual Machines. In this paper we cope with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Thus, optimal placement of cloudlets over wireless access networks and placement of optimal number of VMs in cloudlets appeared to be essential research problems to several researchers because these aspects improve the cloudlet resource utilization significantly [12]. Note that, before the genesis of cloudlets and other edge-computing paradigms, researchers explored various VM migration techniques to optimize the power consumption in Network Function Virtualization (NFV) environments under a dynamic traffic scenario and became aware of its potential benefits [13,14]. The authors of [15] proposed a linear programming solution for computation offloading by considering the QoS requirements of mobile users while maximizing the revenue of service providers.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, optimal placement of cloudlets over wireless access networks and placement of optimal number of VMs in cloudlets appeared to be essential research problems to several researchers because these aspects improve the cloudlet resource utilization significantly [12]. Note that, before the genesis of cloudlets and other edge-computing paradigms, researchers explored various VM migration techniques to optimize the power consumption in Network Function Virtualization (NFV) environments under a dynamic traffic scenario and became aware of its potential benefits [13,14]. The authors of [15] proposed a linear programming solution for computation offloading by considering the QoS requirements of mobile users while maximizing the revenue of service providers.…”
Section: Related Workmentioning
confidence: 99%
“…For this reason, the problem of VNF placement has been attracting increasing attention during the last years [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Nonetheless, the optimal placement of virtual elements to physical resources aimed at minimizing power consumption with service performance constraints for the 5G scenario under study is a complex issue.…”
Section: Related Workmentioning
confidence: 99%
“…However, it is worth mentioning the few works we have found deal with power-based VNF placement proposals [17][18][19][20][21] for our case study. Reference [17] aims at minimizing power consumption allowing users to meet delay requirements using a genetic algorithm approach, while [18,19] propose heuristic algorithms that give power reduction improvement. Besides, [20] presents a suboptimal placement solution that combines traffic and energy cost optimization derived by means of a Markov approximation with matching theory.…”
Section: Related Workmentioning
confidence: 99%
“…Perumal and Murugaiyan [26] have adopted an optimization technique to address the problems of VM placement and consolidation of the server. Eramo et al [27] have presented a unique architecture to solve the problem of dimensioning of server resources using optimization technique. The study outcome was found to possess better energy saving features.…”
Section: A Backgroundmentioning
confidence: 99%